High-strength plastic film and preparation method thereof
By irradiating and grafting modification of convection cast polypropylene film, combined with the coating technology of xanthan gum and nano-silicon dioxide, the problems of insufficient thermal bonding strength and unresistance to high temperature in nitrogen-filled packaging are solved, and plastic films with high strength, impact resistance and excellent sealing performance are achieved.
Patent Information
- Application Number
- CN202411771565.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-28
AI Technical Summary
The thermal strength of plastic films in existing nitrogen-filled packaging is insufficient, resulting in the packaging being easily broken during stacking and transportation, and is not resistant to high-temperature steaming and cooking.
The cast polypropylene film is irradiated and grafted butyl acrylate and maleic anhydride on its surface, and coated with xanthan gum and nanosilica to form a barrier layer to improve sealing performance and thermal bonding strength.
It significantly improves the thermal bonding strength, impact resistance and sealing properties of plastic films, and can maintain good mechanical properties and sealing properties under high-temperature cooking conditions, extending the service life of the packaging.
Smart Images

Figure CN119529361A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic films, and in particular to a high-strength plastic film and a preparation method thereof. Background Art
[0002] As people's demands for living standards improve, product research and development tends to be less additive and pollution-free, and the distribution area is becoming wider and wider. This puts higher demands on product packaging technology to ensure that the product maintains good quality during the distribution process and shelf life.
[0003] Nitrogen-filled packaging is a packaging technology that replaces the gas in the package with nitrogen. As an inert gas, nitrogen can inhibit the reproduction of microorganisms and has no interaction with product ingredients. Placing the product in a nitrogen atmosphere can reduce the oxygen concentration that the product is exposed to, effectively inhibit the physiological activities of microorganisms, the activity of enzymes and the respiration intensity of fresh goods, and achieve the purpose of anti-toxicity, anti-corrosion and preservation. In addition, nitrogen-filled packaging can also prevent the product from being squeezed, deformed, or broken, and can keep the product's appearance intact. However, in order to give full play to the above functions, the packaging materials used should have good performance to keep the nitrogen concentration inside the package at a high level.
[0004] Heat seal strength is the force required to break the heat seal of the packaging bag. The value of this index reflects the sealing strength of the heat seal. However, the gas filled in the package is a double-edged sword. While it protects the food, it will produce a greater impact force on the packaging bag when it is squeezed or collided by external force, requiring the packaging bag to have higher flexibility and sealing strength. Therefore, the heat seal strength of the inflatable packaging is required to be high, thereby reducing the bag breakage rate during stacking and transportation.
[0005] There is more gas in nitrogen-filled packaging, which produces greater squeezing force on the heat-sealed parts. If the heat-sealed strength of the packaging bag is low or over-sealed, the gas in the package will escape from the poorly heat-sealed parts under the squeezing of the gas or as the storage time increases, and even the bag will break. Therefore, good heat-sealed strength is a necessary condition to ensure that nitrogen-filled packaging does not leak and reduce the bag breakage rate.
[0006] High-strength cast polypropylene film (CPP) has the following characteristics: high heat-sealing strength, low heat-sealing temperature; good transparency, high gloss, low haze; excellent pressure resistance, good sealing strength; wide heat-sealing window; optional friction coefficient. Cooking-grade CPP film can be used as a heat-sealing layer to make a cooking packaging material that is resistant to high-temperature cooking and sterilization. Compared with ordinary CPP film, high-temperature cooking CPP film has higher performance requirements, which requires that the film should not break or leak after high-temperature cooking, have high heat-sealing strength, and still maintain good physical properties. At the same time, it can withstand low temperatures and not crack during refrigeration. Summary of the invention
[0007] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high-strength plastic film and a preparation method thereof.
[0008] A method for preparing a high-strength plastic film comprises the following steps: S1, adding butyl acrylate, maleic anhydride and ammonium persulfate into water, stirring for 1-2 hours, and vaporizing at 160-170° C. to obtain pretreated acrylic acid; S2, adoption 60 The cast polypropylene film is irradiated by a Coγ-ray source, and then placed above a vaporization chamber and sprayed with pre-treated acrylic acid on the surface of the irradiated polypropylene film, and then irradiated by a high-pressure mercury lamp and purged with hot air to obtain a pre-treated polypropylene film; S3. Add xanthan gum, nano-silica, carboxyl-terminated polyamide amine and polycarbodiimide into water and stir evenly, apply to the surface of the pretreated polypropylene film, heat treat at 100-120° C. for 10-30 min, and dry.
[0009] Preferably, in S1, the mass ratio of butyl acrylate, maleic anhydride and ammonium persulfate is 5-10:1-3:0.1-0.2.
[0010] Preferably, in S2, 60 The irradiation dose of Coγ-rays is 40-50 kGy.
[0011] Preferably, in S2, the wavelength of the high pressure mercury lamp is 360 nm.
[0012] Preferably, in S2, the high-pressure mercury lamp irradiation treatment is performed for 10-20 minutes, and the irradiation power is 1-5 kW.
[0013] Preferably, in S2, the hot air blowing temperature is 60-70°C.
[0014] Preferably, in S3, the mass ratio of xanthan gum, nano-silica, carboxyl-terminated polyamidoamine, polycarbodiimide, and pretreated polypropylene film is 1-3:1-4:1-2:1-2:100-200.
[0015] Preferably, in S3, the average particle size of nano-silicon dioxide is 80-150 nm.
[0016] Preferably, in S3, the number of generations of the carboxyl-terminated polyamidoamine is 2.0-4.0 generations.
[0017] A high-strength plastic film is prepared by adopting the preparation method of the high-strength plastic film.
[0018] Beneficial effects: The present invention irradiates cast polypropylene film (CPP) to generate free radicals on the surface and form active groups such as peroxy groups and hydroxyl groups, and then grafts butyl acrylate and maleic anhydride on the surface. This not only greatly improves the surface tension of the cast polypropylene film, but also has high heat-sealing strength, good impact resistance and excellent sealing performance. However, the film has poor high temperature resistance, is not resistant to boiling and has poor high-temperature sealing performance.
[0019] The present invention further applies xanthan gum and nano-silicon dioxide to the surface of the pretreated polypropylene film, which not only has a high mutual bonding strength, can effectively form a barrier layer and increase the sealing performance, but also the terminal carboxyl polyamide amine is combined with the nano-silicon dioxide and xanthan gum, the coating has high stability, oxygen and water are difficult to pass through, and the barrier performance is excellent. Through experiments, it is further found that the present invention can withstand high and low temperatures, has high heat sealing strength before and after high-temperature cooking, has good toughness, good mechanical properties, and the product has good sealing performance, is durable, and is not easy to break.
[0020] The high-strength plastic film obtained by the present invention has good toughness, high heat-sealing strength, excellent high-temperature resistance and good sealing performance, and can meet the market demand for such packaging materials. At the same time, the preparation cost is low, the preparation method is simple, and it is suitable for large-scale promotion and production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a comparison chart of the tensile strength and elongation at break of the plastic films obtained in Example 5 and Comparative Examples 1-3.
[0022] Figure 2 It is a comparison chart of the impact strength of the plastic films obtained in Example 5 and Comparative Examples 1-3, and a comparison chart of the oxygen permeability of the plastic films obtained in Example 5 and Comparative Examples 1-3 after being steamed at 135° C. for 30 minutes.
[0023] Figure 3 This is a comparison chart of the heat-sealing strength at 190°C of the plastic films obtained in Example 5 and Comparative Examples 1-3 after being steamed at 135°C for 30 minutes. DETAILED DESCRIPTION
[0024] The present invention will be further explained below in conjunction with specific embodiments.
[0025] The cast polypropylene film used below was purchased from Wenzhou Huaxia Packaging Materials Co., Ltd. and had a tensile strength of 35 MPa, an elongation at break of 540%, and a heat-sealing strength of 20.5 N / 15 mm at 190°C.
[0026] Example 1 A method for preparing a high-strength plastic film comprises the following steps: S1, adding 50g butyl acrylate, 10g maleic anhydride and 1g ammonium persulfate into 400g deionized water and stirring for 1h at a stirring speed of 300r / min, and vaporizing in a vaporization chamber at a vaporization temperature of 160°C to obtain pretreated acrylic acid; S2, adoption 60 The cast polypropylene film was irradiated with a Coγ-ray source at a dose of 40 kGy, placed above the vaporization chamber and sprayed with pre-treated acrylic acid, and then irradiated with a high-pressure mercury lamp with a wavelength of 360 nm for 10 min, an irradiation power of 1 kW, and purged with hot air at 60°C for 30 min to obtain a pre-treated polypropylene film; S3. Add 10g xanthan gum, 10g nano-silica, 10g 2.0-generation carboxyl-terminated polyamide amine and 10g polycarbodiimide into 200g water and stir evenly. Apply the mixture onto the surface of 1000g pretreated polypropylene film by a coating machine, heat treat at 100°C for 10min and dry.
[0027] Example 2 A method for preparing a high-strength plastic film comprises the following steps: S1, adding 100g butyl acrylate, 30g maleic anhydride and 2g ammonium persulfate into 600g deionized water and stirring for 2h at a stirring speed of 500r / min, and vaporizing through a vaporization chamber at a vaporization temperature of 170°C to obtain pretreated acrylic acid; S2, adoption 60 The cast polypropylene film was irradiated with a Coγ-ray source at a dose of 50 kGy, placed above the vaporization chamber and sprayed with pre-treated acrylic acid, and then irradiated with a high-pressure mercury lamp with a wavelength of 360 nm for 20 minutes, an irradiation power of 5 kW, and purged with hot air at 70°C for 30 minutes to obtain a pre-treated polypropylene film; S3, add 30g xanthan gum, 40g nano-silica, 20g 4.0 generation carboxyl-terminated polyamide amine, and 20g polycarbodiimide into 300g water and stir evenly, apply it onto the surface of 2000g pretreated polypropylene film by a coating machine, heat treat at 120°C for 30min, and dry.
[0028] Example 3 A method for preparing a high-strength plastic film comprises the following steps: S1, adding 70g butyl acrylate, 25g maleic anhydride and 1.2g ammonium persulfate into 550g deionized water and stirring for 80min at a stirring speed of 450r / min, and vaporizing in a vaporization chamber at a vaporization temperature of 162°C to obtain pretreated acrylic acid; S2, adoption 60The cast polypropylene film was irradiated with a Coγ-ray source at a dose of 48 kGy, placed above the vaporization chamber and sprayed with pre-treated acrylic acid, and then irradiated with a high-pressure mercury lamp with a wavelength of 360 nm for 12 minutes, an irradiation power of 4 kW, and purged with hot air at 62°C for 30 minutes to obtain a pre-treated polypropylene film; S3. Add 25g xanthan gum, 20g nano-silica, 17g 3.0-generation carboxyl-terminated polyamide amine and 12g polycarbodiimide into 280g water and stir evenly. Apply the mixture onto the surface of 1200g pretreated polypropylene film by a coating machine, heat treat at 115°C for 15min and dry.
[0029] Example 4 A method for preparing a high-strength plastic film comprises the following steps: S1, adding 90g butyl acrylate, 15g maleic anhydride and 1.8g ammonium persulfate into 450g deionized water, stirring for 100min, stirring at a speed of 350r / min, and vaporizing in a vaporization chamber at a vaporization temperature of 168°C to obtain pretreated acrylic acid; S2, adoption 60 The cast polypropylene film was irradiated with a Coγ-ray source at a dose of 42 kGy, placed above the vaporization chamber and sprayed with pre-treated acrylic acid, and then irradiated with a high-pressure mercury lamp with a wavelength of 360 nm for 18 minutes, an irradiation power of 2 kW, and purged with hot air at 68°C for 30 minutes to obtain a pre-treated polypropylene film; S3. Add 15g xanthan gum, 30g nano-silica, 13g 3.0-generation carboxyl-terminated polyamide amine and 18g polycarbodiimide into 220g water and stir evenly. Apply the mixture onto the surface of 1800g pretreated polypropylene film by a coating machine, heat treat at 105°C for 25min and dry.
[0030] Example 5 A method for preparing a high-strength plastic film comprises the following steps: S1, adding 80g butyl acrylate, 20g maleic anhydride, and 1.5g ammonium persulfate into 500g deionized water, stirring for 90min, stirring at a speed of 400r / min, and vaporizing in a vaporization chamber at a vaporization temperature of 165°C to obtain pretreated acrylic acid; S2, adoption 60 The cast polypropylene film was irradiated with a Coγ-ray source at a dose of 45 kGy, placed above the vaporization chamber and sprayed with pre-treated acrylic acid, and then irradiated with a high-pressure mercury lamp with a wavelength of 360 nm for 15 minutes, an irradiation power of 3 kW, and purged with hot air at 65°C for 30 minutes to obtain a pre-treated polypropylene film; S3. Add 20g xanthan gum, 25g nano-silica, 15g 3.0-generation carboxyl-terminated polyamide amine and 15g polycarbodiimide into 250g water and stir evenly. Apply the mixture onto the surface of 1500g pretreated polypropylene film by a coating machine, heat treat at 110°C for 20min and dry.
[0031] Comparative Example 1 A method for preparing a high-strength plastic film comprises the following steps: S1, adding 80g butyl acrylate, 20g maleic anhydride, and 1.5g ammonium persulfate into 500g deionized water, stirring for 90min, stirring at a speed of 400r / min, and vaporizing in a vaporization chamber at a vaporization temperature of 165°C to obtain pretreated acrylic acid; S2, placing the cast polypropylene film above the vaporization chamber and spraying pre-treated acrylic acid on the surface thereof, and then irradiating the film with a high-pressure mercury lamp having a wavelength of 360 nm for 15 minutes, an irradiation power of 3 kW, and hot air blowing at 65° C. for 30 minutes to obtain a pre-treated polypropylene film; S3, adding 20g xanthan gum, 25g nano-silica, 15g 3.0-generation carboxyl-terminated polyamide amine, and 15g polycarbodiimide to 250g water and stirring evenly, coating the mixture on the surface of 1500g pretreated polypropylene film by a coating machine, heat treating the film at 110°C for 20min, and drying the film.
[0032] Comparative Example 2 A method for preparing a high-strength plastic film comprises the following steps: S1, adding 80g butyl acrylate, 20g maleic anhydride, and 1.5g ammonium persulfate into 500g deionized water, stirring for 90min, stirring at a speed of 400r / min, and vaporizing in a vaporization chamber at a vaporization temperature of 165°C to obtain pretreated acrylic acid; S2, adoption 60 The cast polypropylene film was irradiated with a Coγ-ray source at a dose of 45 kGy, placed above the vaporization chamber and sprayed with pre-treated acrylic acid, and then irradiated with a high-pressure mercury lamp with a wavelength of 360 nm for 15 minutes, an irradiation power of 3 kW, and purged with hot air at 65°C for 30 minutes to obtain a pre-treated polypropylene film; S3. Add 20g xanthan gum, 25g nano-silicon dioxide and 15g polycarbodiimide into 250g water and stir evenly. Apply the mixture onto the surface of 1500g pretreated polypropylene film by a coating machine, heat treat at 110°C for 20min and dry.
[0033] Comparative Example 3 A method for preparing a high-strength plastic film comprises the following steps: S1. Adoption 60The cast polypropylene film was irradiated with a Coγ-ray source at a dose of 45 kGy, and then irradiated with a high-pressure mercury lamp at a wavelength of 360 nm for 15 min, an irradiation power of 3 kW, and purged with hot air at 65°C for 30 min to obtain a pretreated polypropylene film. S2. Add 20g xanthan gum, 25g nano-silica, 15g 3.0-generation carboxyl-terminated polyamide amine and 15g polycarbodiimide into 250g water and stir evenly. Apply the mixture onto the surface of 1500g pretreated polypropylene film by a coating machine, heat treat at 110°C for 20min and dry.
[0034] The tensile strength and elongation at break of the plastic films obtained in Example 5 and Comparative Examples 1-3 were measured with reference to GB / T 1040.3-2006 “Determination of tensile properties of plastics Part 3: Test conditions for thin plastics and sheets”.
[0035] like Figure 1 As shown, compared with the original cast polypropylene film, the tensile strength and elongation at break of the plastic films obtained in Example 5 and Comparative Examples 1-3 are greatly increased; and the tensile strength and elongation at break of the plastic film obtained in Example 5 are higher than those of Comparative Examples 1-3 (P < 0.05).
[0036] The impact strength of the plastic films obtained in Example 5 and Comparative Examples 1-3 was measured with reference to GB / T 8809-2015 "Test Method for Pendulum Impact Resistance of Plastic Films". The plastic films obtained in Example 5 and Comparative Examples 1-3 were steamed at 135°C for 30 min, and then the oxygen permeability was tested at 23°C and 80% RH according to "ASTM F1927".
[0037] like Figure 2 As shown, the impact strength and oxygen permeability after cooking of the plastic film obtained in Example 5 are higher than those of Comparative Examples 1-3 (P < 0.05).
[0038] The plastic films obtained in Example 5 and Comparative Examples 1-3 were then steamed at 135°C for 30 min, and then the heat sealing strength at 190°C before and after steaming was tested with reference to QB / T2358-1998 "Test Method for Heat Sealing Strength of Plastic Film Packaging Bags".
[0039] like Figure 3 As shown, the heat sealing strength of the plastic film obtained in Example 5 before and after steaming is higher than that of Comparative Examples 1-3 (P < 0.05).
[0040] The applicant believes that this is because the present invention irradiates the cast polypropylene film (CPP) to generate free radicals on the surface and form active groups such as peroxy and hydroxyl groups, and then grafts butyl acrylate and maleic anhydride on the surface, which not only greatly improves the surface tension of the cast polypropylene film, but also has high heat sealing strength, good impact resistance, and excellent sealing performance, but poor high temperature resistance, and is not resistant to boiling, and has poor high temperature sealing. The present invention further applies xanthan gum and nano-silicon dioxide on the surface of the pretreated polypropylene film, which not only has a high mutual bonding strength, can effectively form a barrier layer, and increase the sealing performance, but also the carboxyl-terminated polyamide amine is combined with nano-silicon dioxide and xanthan gum, the coating has high stability, oxygen and water are difficult to pass through, and the barrier performance is excellent.
[0041] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a high-strength plastic film, characterized in that: The steps include: S1, adding butyl acrylate, maleic anhydride and ammonium persulfate into water, stirring for 1-2 hours, and vaporizing at 160-170° C. to obtain pretreated acrylic acid; S2, adoption 60 The cast polypropylene film is irradiated by a Coγ-ray source, and then placed above a vaporization chamber and sprayed with pre-treated acrylic acid on the surface of the irradiated polypropylene film, and then irradiated by a high-pressure mercury lamp and purged with hot air to obtain a pre-treated polypropylene film; S3. Add xanthan gum, nano-silica, carboxyl-terminated polyamide amine and polycarbodiimide into water and stir evenly, apply to the surface of the pretreated polypropylene film, heat treat at 100-120° C. for 10-30 min, and dry.
2. The method for preparing a high-strength plastic film according to claim 1, characterized in that: In S1, the mass ratio of butyl acrylate, maleic anhydride and ammonium persulfate is 5-10:1-3:0.1-0.
2.
3. The method for preparing the high-strength plastic film according to claim 1, characterized in that: In S2, 60 The irradiation dose of Coγ-rays is 40-50 kGy.
4. The method for preparing the high-strength plastic film according to claim 1, characterized in that: In S2, the wavelength of the high pressure mercury lamp is 360 nm.
5. The method for preparing the high-strength plastic film according to claim 1, characterized in that: In S2, the high-pressure mercury lamp irradiation treatment is performed for 10-20 minutes, and the irradiation power is 1-5kW.
6. The method for preparing a high-strength plastic film according to claim 1, characterized in that: In S2, the hot air blowing temperature is 60-70°C.
7. The method for preparing a high-strength plastic film according to claim 1, characterized in that: In S3, the mass ratio of xanthan gum, nano-silica, carboxyl-terminated polyamide amine, polycarbodiimide, and pretreated polypropylene film is 1-3:1-4:1-2:1-2:100-200.
8. The method for preparing a high-strength plastic film according to claim 1, characterized in that: In S3, the average particle size of nano-silicon dioxide is 80-150nm.
9. The method for preparing a high-strength plastic film according to claim 1, characterized in that: In S3, the generation number of the carboxyl-terminated polyamidoamine is 2.0-4.0 generations.
10. A high-strength plastic film, characterized in that: The high-strength plastic film is prepared by the method for preparing the high-strength plastic film according to any one of claims 1 to 9.